2015
DOI: 10.5901/ajis.2015.v4n3s1p196
|View full text |Cite
|
Sign up to set email alerts
|

Water Management in the Private Domain: A Comparative Analysis of Urban Water Management Practice in Nigeria’s Niger Delta

Abstract: The paper compares three contextually different urban areas in Nigeria's Niger Delta to understand how private involvement in the management of water has affected the spatial and socio-economic circumstances of the population. A wide range of methods including semi-structured interviews, observations and analysis of secondary records were used to collect data. The paper observed different forms of private water services including commercial/private borehole, sachet/bottled water services, mobile supplies etc. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Current water supply efforts of government are concentrated in the urban areas. It is reported that the highest urban population that have access to public water services is 3.8% for Uyo, while 90% of the state rural water projects are either neglected, abandoned, non-functional or uncompleted [4,5]. In the rural areas, however, there is a high dependence on all forms of natural sources of water for domestic use (e.g., streams, river, rain, wells).…”
Section: Introductionmentioning
confidence: 99%
“…Current water supply efforts of government are concentrated in the urban areas. It is reported that the highest urban population that have access to public water services is 3.8% for Uyo, while 90% of the state rural water projects are either neglected, abandoned, non-functional or uncompleted [4,5]. In the rural areas, however, there is a high dependence on all forms of natural sources of water for domestic use (e.g., streams, river, rain, wells).…”
Section: Introductionmentioning
confidence: 99%